The Characteristics of the Nature of Science (NOS)-based Instruments in Newton Law Using Rasch Model Analysis - Murti, Pratiwi Restu; Aminah, Nonoh Siti; Harjana, Harjana (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
The objective of this research is to find out the characteristic of each test item with NOS-based instruments which is analysed based on validity and reliability level using Rasch model (RM). A test using NOS-based instruments was used to collect the data. This research is categorized as descriptive with quantitative using statistic from RM through QUEST program. There are 104 students participated as the subject of this research. The result, which is based on validity of each test item using RM analysis, shows that 25 test items are considered fit or accepted. Based on the estimate of item reliability, NOS-based instrument has reliability coefficiency at 0.96. Based on difficulty items 2 test items declared not good, namely test item number 19 and item test number 4. Based on the analysis according to Classic Test Theory of RM, the NOS instrument can be used to measure senior high school students' science literacy on Newton Law.